Kompetensi Mutlak Badan Penyelesaian Sengketa Konsumen Dalam Sengketa Lelang Barang Gadai: Studi Putusan Nomor 16 PK/Pdt.Sus-BPSK/2020 - Mario Ari Leonard, Barus; Anindita, Sri Laksmi (UI Scholars Hub, 2023)
The authority of Consumer Dispute Settlement Agency (BPSK) in settling consumer dispute is regulated in a limited cause. In the Verdict No. 16 PK/Pdt.Sus-BPSK/2020, Judges verdict that BPSK has no authority in giving verdict for settling dispute between pawn giver and pawn taker in the case of pawn auction. This happen though the verdict of BPSK has been approved by Judges of first degree court and appellate court. The verdict was analyzed in this writing with the qualitative method. BPSK is alternative dispute resolution board between consumer and business industry. Agreement with pawn company and pawn giver was mainly debt agreement, not agreement between consumer and business industry, therefore BPSK has no authority in in settling the dispute. In which, pawn auction dispute must be submitted to the court not BPSK.